Drawing from the wellspring. - Derges, Susan (Resurgence & Ecologist)
The article discusses the symbiotic relationship with water. Topics mention including the photographs of the gem like mirrors of the rock as part of the making a marine environment project, learning to control the temperature, oxygen and salinity content and important participation of imagination and insight.